Uji Fitokimia dan Toksisitas Ekstrak Etil Asetat Kulit Batang Melochia umbellata (Houtt) Stapf. var. Visenia dengan Metode Brine Shirmp Lethality Test (BSLT) - Ahmad, Fauziah; Soekamto, Nunuk H.; Firdaus, Firdaus (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2017)
Melochia umbellata (Houtt) Stapf. var. Visenia is plant species included in Malvaceae family. This spesies is known as paliasa and used as traditional medicine by the people of South Sulawesi. This study aimed to determine the secondary metabolites by reagents and toxicity characteristic testing from bark extract of Melochia umbellata (Houtt) Stapf. var. Visenia using Brine Shirmp Lethality Test (BSLT) method. The extract was prepeared by maceration ethyl acetate. Phytochemical test result showed that the ethyl acetate extract was containing the steroid compound, alkaloids and terpenoids. Toxicity test performed by shrimp Artemia salina Leach larvae was at 48 hours. The toxic effects of the extract were identified by the percentage of the number of shrimp larvae mortality using probit value analysis (LC50). The toxicity test of bark Melochia umbellata (Houtt) Stapf. var. Visenia extract showed that the ethyl acetate extract is toxic to A. salina LC50 = 54,55 mg / mL.